Endovascular management of Wunderlich syndrome - Phani Chakravarty Mutnuru; Rahul Devra; S. S. S. Dheeraj; Sridevi Chinta (Journal of Clinical and Scientific Research)
Wunderlich syndrome (WS) is a spontaneous, non-traumatic retroperitoneal haemorrhage confined to the subcapsular or perinephric spaces. Various neoplastic and non-neoplastic pathologies can cause this entity, renal angiomyolipoma being the most common. Early accurate diagnosis and timely intervention are required for a favourable outcome. We present the case of a 37-year-old female with no previous comorbidities who developed severe pain in the left loin since 1 day after a fall from a chair. Ultrasonography abdomen done in outside hospital revealed massive splenomegaly with perisplenic haematoma and moderate haemoperitoneum. Contrast-enhanced computed tomography abdomen showed bilateral renal angiomyolipomas with intralesional aneurysms and active bleeding on the left side. In view of active contrast leak and fall in haemoglobin %, endovascular embolisation was done through right transfemoral arterial access. The patient was discharged in stable condition. During 1-month follow-up, the patient is asymptomatic.